(NoSNOWY NAU^NYH ISSLEDOWANIJ (B:s (NrADIO\LEKTRONIKA (B: (Nu^EBNOE POSOBIE (B/s - (NbABUROW(B, (N|DUARD fEDOROWI^s; (NkULIKOW(B, (N|DUARD lEONIDOWI^s; (NmARIGODOW(B, (NwLADIMIR kONSTANTINOWI^s ((NkIEW (B:s (NwY]A [K(B,s, 1988)
(NbIBLIOGR(B.: (NS(B. 223-227 (73 (NNAZW(B.)s
Keywords: (NrADIO\LEKTRONIKAs